Experimental Study on Fracturing Fracture Deformation Mechanism of Shale Reservoir - Xiang, Zuping; Ding, Yangyang; Ao, Xiang; Zhong, Zhicong; Li, Zhijun; Xiao, Hui; Chen, Zhonghua; Xiao, Qianhua; Ma, Xinjian (Frontiers in Energy Research, 2022)
After large-scale sand fracturing of horizontal wells in shale gas reservoir, fracturing fractures will deform in the production process. However, fracture deformation will lead to the decrease in fracture conductivity and then cause the decrease of gas well productivity. Therefore, in order to evaluate the fracturing fracture deformation mechanism of shale reservoirs, the shale proppant-supported fracture deformation evaluation experiments were carried out under different proppant types, particle sizes, sanding concentrations, and closure pressure conditions, respectively, and the variation curves of fracture width was calculated by a stereomicroscope under different experimental conditions. Then based on the experimental results, the fracture sensitivity factors and fracture deformation mechanism were analyzed, and the deformation mechanisms of fracturing fractures affected by proppant embedding and crushing were studied emphatically. The analysis results of fracture sensitivity factors indicate that the larger the particle size and hardness of proppant, the lower the sand concentration, proppant embedded on the shale rock surface. Moreover, the deeper the proppant is embedded, the faster the fracture conductivity decreases. In addition, the greater the closure pressure, the more serious is the proppant embedment, and the faster the fracture width decreases. The analysis results of fracture deformation mechanism show that, on the on hand, under variable closure pressure, the proppant with larger hardness and larger particle size is used for fracturing, and the proppant embedded in the fracture surface is the main cause of fracture deformation. However, if only the sand concentration of the proppant in the fracture is changed, the fracture deformation is jointly dominated by the embedding and crushing of the proppant. On the other hand, under constant closure pressure, the main mechanism of fracture deformation is that the proppant is embedded into the fracture surface when the closure pressure is low, but if the closure pressure is high, the main mechanism of fracture deformation is the crushing and compaction of proppant.